2021
DOI: 10.1109/access.2021.3085601
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Value of Intra- and Peri-Tumoral PET/CT Radiomics for Outcome Prediction in Head and Neck Cancer

Abstract: To investigate the prognostic value of peri-tumoral radiomics features of pre-treatment PET/CT images in patients with head and neck cancer. 166 patients from 4 centers (111 for training and 55 for external independent testing) were retrospectively analyzed. 11 regions were used for feature extraction, (1) Intra-tumoral region (Intra) was first dilated radially along the edge by 3, 6, 9, 12 and 15 mm to obtain (2) 5 solid combined regions (noted as Comb_3, 6, 9, 12, and 15, respectively), and (3) 5 hollow annu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Several studies have shown that radiomics in CT has the potential to improve the prediction of the prognosis of H&N cancer [ 23 , 24 , 25 ]. Some studies have also investigated the use of radiomics in both CT and PET for survival analysis for H&N cancer [ 26 , 27 ]. While these studies investigate the prognostic potential of CT and PET radiomics based on primary tumour delineation, there is a need to quantify the prognostic potential of radiomics features extracted from different regions of interest (ROI) such as the primary tumour and lymph nodes.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that radiomics in CT has the potential to improve the prediction of the prognosis of H&N cancer [ 23 , 24 , 25 ]. Some studies have also investigated the use of radiomics in both CT and PET for survival analysis for H&N cancer [ 26 , 27 ]. While these studies investigate the prognostic potential of CT and PET radiomics based on primary tumour delineation, there is a need to quantify the prognostic potential of radiomics features extracted from different regions of interest (ROI) such as the primary tumour and lymph nodes.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we used supervoxel-based contour randomization (24) to create perturbed ROIs in PET and CT images of 60 randomly selected patients, respectively. Having 60 patients (120 PET and CT ROIs) perturbed would have made it possible to assess the robustness of feature extraction (34)(35)(36). Furthermore, due to the perturbed ROIs may deviate from tumor region, even include some non-tumor slices (Supplementary Figure S1), which may leads to unnecessary removal of features in robustness assessment, the perturbed results were further checked and adjusted slice by slice, which is also a time-consuming process.…”
Section: Discussionmentioning
confidence: 99%
“…Five HNC data collections consisting of a total of 806 patients from 9 centers were obtained: (1) The Head-Neck-PET-CT collection provided by Vallières et al, including 296 patients from 4 centers in Canada, i.e., Centre hospitalier de l’Université de Montréal (CHUM, n = 65), Centre hospitalier universitaire de Sherbrooke (CHUS, n = 100), Hôpital général juif (HGJ, n = 90) de Montréal, and Hôpital Maisonneuve-Rosemont (HMR, n = 41) de Montréal. Our previous studies [ 27 , 28 ] on multi-level multi-modality fusion radiomics and peri-tumor radiomics were conducted based on this collection. (2) The HNSCC collection provided by Grossberg et al included 159 patients from the MD Anderson Cancer Center, denoted as MDACC.…”
Section: Methodsmentioning
confidence: 99%